Influence of Actor's Congruent and Incongruent Gaze on Language Processing - Abashidze, Dato; Knoeferle, Pia (Frontiers in Psychology, 2021)
In interpreting spoken sentences in event contexts, comprehenders both integrate their current interpretation of language with the recent past (e.g., events they have witnessed) and develop expectations about future event possibilities. Tense cues can disambiguate this linking but temporary ambiguity in their interpretation may lead comprehenders to also rely on further, situation-specific cues (e.g., an actor’s gaze as a cue to his future actions). How comprehenders reconcile these different cues in real time is an open issue that we must address to accommodate comprehension. It has been suggested that relating a referential expression (e.g., a verb) to a referent (e.g., a recent event) is preferred over relying on other cues that refer to the future and are not yet referentially grounded (‘recent-event preference’). Two visual-world eye-tracking experiments compared this recent-event preference with effects of an actor’s gaze and of tense / temporal adverbs as cues to a future action event. The results revealed that people overall preferred to focus on recent (vs. future) events in their interpretation, suggesting that while congruent and incongruent gaze cues can jointly with verb tense override the recent-event preference, the latter still plays a key role in shaping participants’ interpretation. Additional post-experimental memory tests provided insight into the longevity of the gaze effects.